Local Government Financing in TVET: A Study of Gandaki Province of Nepal - Paudel, Prakash Kumar; Parajuli, Mahesh Nath; Bhattarai, Prakash Chandra; Gautam, Suresh; Shrestha, Milan; Bhurtel, Anup (Journal of Training and Development, 2026)
The national policy in Nepal, particularly after the promulgation of the new constitution in 2015, emphasizes the role of local governments in designing, implementing, and monitoring Technical and Vocational Education and Training (TVET). Despite policy priority, households, the private sector, and other non-government organizations primarily share TVET costs. The contribution from these sources varies from unit to unit, from time to time, and from place to place. This variation in financing has often created problems, such as a lack of funds and inconsistencies in designing and implementing TVET among different government agencies and tiers. With this context, this study explains how local governments are prepared to finance TVET and provide access to it for youth employment. We detail allocation, particularly in their investment in TVET and sources of funding made by local governments in Gandaki Province of Nepal. This would help in understanding the priority of the local governments in designing, implementing, and monitoring the TVET sector. The data were collected from secondary sources (SUTRA – a financial management system managed by the government of Nepal). This study found that the local governments in Gandaki province allocated a minimal budget from their internal source in three consecutive fiscal years (2019-2022), which reveals the fact that local governments are yet to prioritize this as the TVET budget shares only about 5% of the total budget. The findings also show that almost all the budget goes to short-term training programmes and the long term formal TVET gets little attention. Further, the study also found TVET at local governments are largely financed by external sources.